2001
DOI: 10.1136/gut.49.4.506
|View full text |Cite
|
Sign up to set email alerts
|

Guinea pig transglutaminase immunolinked assay does not predict coeliac disease in patients with chronic liver disease

Abstract: Background-It has been suggested that serological screening for coeliac disease (CD) should be performed in patients with chronic unexplained hypertransaminasaemia. Aims-To evaluate the specificity for CD diagnosis of serum IgA antitissue transglutaminase (tTG) determination in consecutive patients with chronic hypertransaminasaemia using the most widely utilised ELISA based on tTG from guinea pig as the antigen. Patients and methods-We studied 98 patients with chronic hypertransaminasaemia, evaluated for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
3
6

Year Published

2003
2003
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 22 publications
5
29
3
6
Order By: Relevance
“…A high prevalence of anti-tTG antibodies with no evidence of CD has been reported in diverse diseases such as diabetes, autoimmune diseases, Down syndrome, and inflammatory bowel disease (4,6,37), as well as in chronic liver diseases (8,43). It has been suggested that the low specificity of anti-tTG antibodies could be attributed to the utilization of transglutaminase from guinea pig liver as an antigen source (25) and that the use of recombinant tTG may abolish this pitfall (8). Furthermore, the high immunoglobulin levels and other immunological disturbances observed in such patients might interfere with anti-tTG ELISAs (43).…”
Section: Discussionmentioning
confidence: 99%
“…A high prevalence of anti-tTG antibodies with no evidence of CD has been reported in diverse diseases such as diabetes, autoimmune diseases, Down syndrome, and inflammatory bowel disease (4,6,37), as well as in chronic liver diseases (8,43). It has been suggested that the low specificity of anti-tTG antibodies could be attributed to the utilization of transglutaminase from guinea pig liver as an antigen source (25) and that the use of recombinant tTG may abolish this pitfall (8). Furthermore, the high immunoglobulin levels and other immunological disturbances observed in such patients might interfere with anti-tTG ELISAs (43).…”
Section: Discussionmentioning
confidence: 99%
“…Although they performed well in general use, there were many more false positives in patients with chronic liver disease. 83 This was probably due to the antigens present in the crude extract of pig liver and perhaps also to immune dysregulation (hypergammaglobulinemia) associated with the chronic liver disease itself. The specificity was improved when the tTG reagent was either derived from human red cells or generated recombinantly from human tTG sequences.…”
Section: Anti-tissue Transglutaminase Antibody and Endomysial Antibodiesmentioning
confidence: 99%
“…The specificity was improved when the tTG reagent was either derived from human red cells or generated recombinantly from human tTG sequences. [83][84][85] However, occasionally false positives are seen even with the human tTG assays, especially in patients with advanced chronic liver disease. This may be due to the development of antibodies directed against tTG in the diseased liver.…”
Section: Anti-tissue Transglutaminase Antibody and Endomysial Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The recombinant human assay can reduce the higher FP rate obtained with guinea pig tTGA in patients with hypertransaminasemia (27 ).…”
Section: Clinical Chemistrymentioning
confidence: 99%